Parenting Style and Stimulation of Psychosocial Development on the Psychosocial Development of Pre-School Children with Stunting - Risa Nurhayati; Sefrina Rukmawati; Rahayu Budi Utami; Deppi Nurmalita; Paradita Ayu Rahma (Jurnal Kesehatan, 2024)
Stunting is a condition of impaired growth in children under five caused by chronic malnutrition, particularly within the first 1,000 days of life, resulting in children being too short for their age. This issue is crucial because stunting also impacts children's motor skills and psychosocial development. The problem of malnutrition predominantly occurs in developing countries, where approximately 80% of stunted children are found in 24 countries across Asia and Africa. Indonesia has the highest prevalence, followed by India, China, Nigeria, and Pakistan. This study analyzes the influence of parenting styles and psychosocial stimulation on preschool-aged children experiencing stunting development. The research design uses an analytical observational method with a cross-sectional approach. The study sample consists of stunted children aged 3-6 years and their parents in Nganjuk Regency, totaling 150 respondents. Sampling was conducted purposively, and data were collected through the PSDQ questionnaire for parenting style, the EC HOME for psychosocial stimulation, and the KMME for psychosocial development. Multiple linear regression analysis was employed, with a significance level of (α=0.05). The analysis results indicate a significant effect of psychosocial stimulation on the psychosocial development of stunted children, with a p-value of 0.001≤α=0.05. Responsive parenting and active parent-child interaction are crucial in supporting children's development. Therefore, it is essential to improve children's nutritional status through proper caregiving approaches to ensure they grow with normal nutritional status and achieve optimal development in the future.